High-frequency analysis of foreign exchange interventions: what do we learn? - Lukas Menkhoff (Center for Economic Studies and ifo Institute (CESifo), 2008)
The high-frequency analysis of foreign exchange dynamics is helpful in order to better identify the impact of central bank interventions. Evidence robustly shows that interventions do indeed move the exchange rate level in the desired direction. Interventions increase volatility in the short run as they are regarded as information; but they can reduce volatility overall. Ways of transmission may reach beyond the signaling channel and also include the portfolio balance and a damping channel. Finally, interventions are more successful if they obey certain conditions, such as being coordinated among central banks and going with the market and fundamentals.
Keywords: F31; G14; G15; E44; 330; Foreign exchange; central bank intervention; high-frequency data; transmission channel; Wechselkurspolitik; Internationale wirtschaftspolitische Koordination; Transmissionsmechanismus; Wechselkurs; Volatilität; Wirtschaftspolitische Wirkungsanalyse; Welt